Corrosion behavior of 5-hydroxytryptophan (HTP)/epoxy and clay particle-reinforced epoxy composite steel coatings. Issue 1 (1st January 2020) - Ngasoh, Odette Fayen; Anye, Vitalis Chioh; Agyei-Tuffour, Benjamin; Oyewole, Oluwaseun K.; Onwualu, Peter Azikiwe; Soboyejo, Winston O.
Abstract: The corrosion behavior of 5-hydroxytryptophan (HTP), and clay particulate reinforced epoxy coatings is studied on a steel substrate that is used widely in pipelines and tanks. The corrosion behavior was studied in sodium chloride (3.5 wt. % NaCl) solutions that simulate potential seawater exposure at pH 3 and 7. X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM) were used for microstructural characterization of the samples. The thermal stability was characterized using Thermogravimetric Analysis (TGA). The underlying corrosion reactions and reaction products were also elucidated via Fourier Transform Infrared Spectroscopy (FTIR). Electrochemical impedance spectroscopy (EIS) and in-situ observations of interfacial blisters were used to study the underlying degradation mechanisms. Electrochemical impedance spectroscopy revealed that for prolonged exposure of about 90 days and above, the composite materials exhibited better corrosion resistance at a pH of 3 as seen by the higher diameter of the Nyquist plot. Fewer corrosion products were observed on the scribed areas of the HTP samples in the scribe test in pH of 3 corroding environment. This signifies improved adhesion of the coatings in that environment for the HTP/epoxy coatings. The results obtained also show that a 1 mm blister size was observed in the pristine epoxy sample while no blisters were observed in the clay/epoxy and HTP/epoxy samples exposed at pH of 3. In the pH 7 environment, the EIS experiment revealed the presence of blisters with diameters in the range of 1–4 mm, after exposure for 90 days. The implications of the results are discussed for the corrosion protection of steel surfaces with composite coatings.